KONSEP JIHAD DALAM KUTUB AT-TIS’AH (STUDI MAUDU’I) - Rohmansyah (Al-Majaalis : Jurnal Dirasat Islamiyah, 2016)
Based on the results of the study, there are about 146 hadith; between 54 jihâd concept and 92 suport jihâd hadith that have been collected from Kutub at-Tis’ah that result in the concept of jihâd, which is the definition of the jihâd, the kinds of the jihâd, the procedure of the jihâd, and the philosophy of the jihâd. The jihâd means mobilizing all of the capabilities in terms of spirits and materials and avoiding blamable conducts in order to be close to Allah SWT. Additionally, the jihâd also means learning religious knowledge and teaching others the knowledge. The kinds of the jihâd include the jihâd against polytheists (musyrik), the jihâd against desires, and the jihâd against tyrant. The procedure of the jihâd includes good intention (niat), parental permission, organized collectively, and under the command of a leader. The philosophy of the jihâd is to spread Islamic knowledge, to deny hostility and evil, to protect and to defend self and possessions, to express truth and justice, to socialize good and noble conduct and to materialize Islamic values in social, national and state lives.